2013
DOI: 10.1038/ncomms3780
|View full text |Cite
|
Sign up to set email alerts
|

Janus cyclic peptide–polymer nanotubes

Abstract: Self-assembled nanotubular structures have numerous potential applications but these are limited by a lack of control over size and functionality. Controlling these features at the molecular level may allow realization of the potential of such structures. Here we report a new generation of self-assembled cyclic peptide-polymer nanotubes with dual functionality in the form of either a Janus or mixed polymeric corona. A 'relay' synthetic strategy is used to prepare nanotubes with a demixing or mixing polymeric c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
92
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(100 citation statements)
references
References 70 publications
8
92
0
Order By: Relevance
“…42,43 Cyclic, (hyper-)branched and multiarm star architectures with three or more segments have not received less attention as building blocks for MCNs formation so far, but individual studies give a glimpse of their structuring potential. [44][45][46][47][48] Monomer functionality. The strength of microphase separation depends on the segment-segment incompatibility, χ, which is an intrinsic property of the employed monomers and higher values correspond to stronger enthalpic repulsion.…”
Section: Controlled and Directed Self-assemblymentioning
confidence: 99%
“…42,43 Cyclic, (hyper-)branched and multiarm star architectures with three or more segments have not received less attention as building blocks for MCNs formation so far, but individual studies give a glimpse of their structuring potential. [44][45][46][47][48] Monomer functionality. The strength of microphase separation depends on the segment-segment incompatibility, χ, which is an intrinsic property of the employed monomers and higher values correspond to stronger enthalpic repulsion.…”
Section: Controlled and Directed Self-assemblymentioning
confidence: 99%
“…41 The desired cyclic peptide chain transfer agent CP-PABTC 3 was then obtained by coupling the chain transfer agent (CTA) N-hydroxysuccinimide (propanoic acid)yl butyl trithiocarbonate (NHS-PABTC, 1) to the lysine residues of CP 2 (Scheme 1). Mass spectrometry monitoring indicated that the coupling reaction was quantitative, as no residual CP 2 or mono-functionalized product was detected, affording CP-PABTC 3 in high yield.…”
Section: Synthesis Of the Cyclic Peptide Chain Transfer Agentmentioning
confidence: 99%
“…41 Despite the numerous individual approaches to create CPpolymer conjugates, no comprehensive comparison between the grafting-from and the grafting-to approach has been reported. Therefore, we designed this systematic study comparing the two approaches to clearly determine the advantages and disadvantages of each strategy.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Perrier's group adopted a click chemistry reaction to couple a cyclic l , d ‐α‐peptide pattern to various responsive polymers. Hybrids with different degrees of functionalization and sensitivity to the environmental stimuli were produced …”
Section: Dl‐α‐peptide‐based Building Blocks To Generate Hybrid Matermentioning
confidence: 99%